PECULIARITIES OF CONTROLLING THE PROCESS AND RESULTS OF FORMING METHODOLOGICAL COMPETENCE OF FUTURE FOREIGN LANGUAGE TEACHERS IN THEIR SELF-DEPENDENT WORK - Nataliia Mayer (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article reveals peculiarities of controlling the process and results of forming methodological competence of future teachers of foreign languages in their self-dependent work in specially designed and developed information-communicative teaching environment. There is suggested the author understands of the notion "controlling the process and result of forming methodological competence" and described the peculiarities of self-control by master's degree students. Determined didactic function control (feedback, corrective, training, evaluation), which designed both the teacher activity and the activity of undergraduates. The features of realization evaluation function in assessing a teacher and self-assessment of their educational activities undergraduates in different types of control, which form an individual. Formulated conditions that made possible the objectivity and validity of student assessment magistracy. There are defined objects and means of control over the level of improvement in methodological competence components. The article justifies the criteria of evaluating methodological knowledge as well as methodological skills in compiling a summary plan for a practical lesson and a script for an out-of-auditorium measurement in foreign language under real conditions of organizing process during pedagogical practice of master's degree students.